PENGARUH SUBSTITUSI LARVA BLACK SOLDIER FLY (Hermetia illucens) PADA RANSUM TERHADAP PERFORMA BEBEK PEDAGING HIBRIDA - M. Nico Agastya Maulana; Sefri Ton; M. Habbib Khirzin; Nadia Maharani; Dwi Ahmad Priyadi (Politeknik Pertanian Negeri Kupang, 2023)
The aim of the study was to determine the effect of Black Soldier Fly larvae substitution in the ration on duck performance. This study used a randomized block design with three treatments and six replications (P0: 0% BSF larvae, P1: 10% BSF larvae, and P2: 20% BSF larvae). The research parameters are body weight gain, feed consumption, feed conversion ratio (FCR), and final body weight. The results showed that the substitution treatment of BSF larvae in the ration had a significant effect (P<0.05) on body weight gain. Average body weight of ducks ranged from 176.13–195.80gr/head. The substitution treatment of BSF larvae had a significant effect (P<0.05) on the FCR of ducks. The average FCR of ducks ranges from 1.70 – 1.79g/head. The conclusion of the study was that substitution of 20% fresh BSF larvae in the ration (P2) gave the best results on duck performance.Keyword: Black Soldier Fly Larvae, Duck, Feed Substitution, Performance